2016
DOI: 10.5539/ijc.v9n1p38
|View full text |Cite
|
Sign up to set email alerts
|

The Golden Series and Clusters of Gold-unique Shapes and Bonding

Abstract: Golden clusters have been analyzed and categorized using the series method. They have been found to be intensely capped. The complexity of capping is likely responsible for the unique shapes of clusters. The predicted structures of the golden clusters with one or two nuclear indices have been found to be in agreement with the observations from structural determinations. According to the series, the golden clusters have tendency of occurring in an overlapping area which is normally dominated by naked metal clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The 4n(14n) series method developed in this work, in which n represents the number of skeletal elements in a cluster, can be used to categorize a wide range of clusters, among others, transition metal carbonyls, boranes, heteroboranes, metalloboranes, Zintl ions, and gold clusters (Kiremire, 2015a(Kiremire, , 2015b(Kiremire, ,2016c(Kiremire, ,2016d(Kiremire, , 2017. Using the series formula, the number of valence electrons of a given cluster can easily be calculated directly without counting the valence electrons of individual skeletal atoms and ligands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 4n(14n) series method developed in this work, in which n represents the number of skeletal elements in a cluster, can be used to categorize a wide range of clusters, among others, transition metal carbonyls, boranes, heteroboranes, metalloboranes, Zintl ions, and gold clusters (Kiremire, 2015a(Kiremire, , 2015b(Kiremire, ,2016c(Kiremire, ,2016d(Kiremire, , 2017. Using the series formula, the number of valence electrons of a given cluster can easily be calculated directly without counting the valence electrons of individual skeletal atoms and ligands.…”
Section: Resultsmentioning
confidence: 99%
“…The use of skeletal numbers to categorize clusters has been done (Kiremire, 2017). This is yet another area where skeletal numbers are extremely useful.…”
Section: Categorization Of Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the series method is generally very precise in categorizing and predicting the shapes of clusters such as boranes and their relatives, carbonyl and Zintl clusters (Kiremire, 2016a). The categorization of some golden clusters has been done using skeletal numbers and some of the work published (Kiremire, 2016b(Kiremire, , 2016c(Kiremire, , 2017. In this paper the emphasis is to closely focus mainly on selected samples of capped golden clusters whose nuclei are comprised of two skeletal elements.…”
Section: Introductionmentioning
confidence: 99%